2019
DOI: 10.1097/md.0000000000015100
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the efficacy of Chinese herbal medicines in the treatment of primary dysmenorrhea

Abstract: Introduction: Chinese herbal medicines (CHM) have been commonly used in the treatment of primary dysmenorrhea in East Asia. Several systematic reviews have been conducted to assess the clinical efficacy of CHM in the treatment of primary dysmenorrhea. However, their comparative efficacy is still unclear. Therefore, the purpose of this study is to conduct a network meta-analysis (NMA) to systematically compare the advantages of different CHM in the treatment of primary dysmenorrhea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, at present, the treatment of PD in modern medicine is mostly symptomatic treatment, and there is no speci c drug. Western medicine analgesic treatment can only alleviate the clinical symptoms, can not be completely cured, can not achieve the desired therapeutic effect [17][18][19][20] . The treatment of PD with traditional Chinese medicine has a rich theoretical system and clinical experience, and it is regarded as an advantageous disease in the treatment of traditional Chinese medicine 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, the treatment of PD in modern medicine is mostly symptomatic treatment, and there is no speci c drug. Western medicine analgesic treatment can only alleviate the clinical symptoms, can not be completely cured, can not achieve the desired therapeutic effect [17][18][19][20] . The treatment of PD with traditional Chinese medicine has a rich theoretical system and clinical experience, and it is regarded as an advantageous disease in the treatment of traditional Chinese medicine 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“… 73 In addition, research on traditional Chinese medicine and herbal medicine for dysmenorrhea treatment has also been a hotspot in recent years. 74 Among them, Shaofu-Zhuyu decoction can effectively relieve menstrual pain. 75 , 76 Transcutaneous electrical nerve stimulation, acupuncture, and surgical interventions have also been shown to relieve menstrual pain.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbal medicines (CHM) are well-accepted in the treatment of primary dysmenorrhea in East Asia, such as China, Korea, and Japan. Reviews from Gao et al [57] showed a significant advantage compared with other treatments. Sharghi et al [27] demonstrated that medicinal plants, drugs, and acupressure seem to suppress pain by reducing the level of prostaglandins, mediating nitric oxide, increasing beta-endorphin levels, blocking the calcium channel, and enhancing circulatory flow through the uterine pathway.…”
Section: Mini Reviewmentioning
confidence: 99%